Two rare cases of primary clear cell adenocarcinoma of the urethra: clinical experience, case report and literature review - Jiang, Bohao; Hu, Jiyuan; Wang, Benqiao; Liu, Xujia; Tong, Ling; Xu, Yitong; Zhang, Hao (Frontiers in Oncology, 2025)
BackgroundPrimary clear cell adenocarcinoma of the urethra (CCAU) is a kind of extremely rare genitourinary cancer. Despite the similarity in the clinical manifestations of these reported cases, diagnosis and determination of standard therapy remain challenging due to the rarity of findings and similarity with other urethral tumors.Case presentationHerein, we reported two cases of CCAU with the same chief complaint of hematuria: a 71-year-old female and a 66-year-old male. The male patient reported concomitant symptoms of frequent and painful urination. CT scans show abnormal enhancements. After a cystoscopy examination, both patients are diagnosed with malignant urethral tumors. Surgical resections and additional pathological examinations support the diagnosis of CCAU (palliative resection for case 1 and transurethral resection for case 2). Case 1 undergone progression 6 months after initial treatment with transurethral resection and chemotherapy with a 15-month overall survival. In contrast, the prognosis of case 2 remained uneventful 10 months after surgery without recurrence. After presenting our cases, we launched a literature review that included 23 articles and 33 cases of CCAU to summarize the characteristics of the disease.ConclusionPrimary clear cell adenocarcinoma of the urethra is a rare malignant urethral tumor with controversial histological origins. Primary symptoms include hematuria and changes in voiding habits. Middle-aged and elderly females are more susceptible to primary clear-cell adenocarcinoma of the urethra. Unfortunately, it is difficult to differentiate primary clear-cell adenocarcinoma of the urethra from other urethral tumors due to similar clinical features. However, imaging tools such as CT, MRI, and cystoscopy are adjunctive in confirming diagnoses. Even though surgical resection is the primary treatment to relieve clinical symptoms, prevent recurrence, and confirm diagnosis, no standard surgical protocol is available. The therapeutic effect of postoperative adjuvant therapies remains unclear. Future investigations on CCAU are necessary to advance clinical knowledge and to provide treatment guidance.